The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010 Sixth Advanced International Conference on Telecommunications 2010
DOI: 10.1109/aict.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Occupancy in an Urban Environment: A Cognitive Radio Approach

Abstract: Due to the ever-increasing number of radio communication technologies, lack of frequency spectrum has become a serious problem recently. Cognitive Radio (CR) technology promises to be one possible solution to this problem, by allowing access of unlicensed users in licensed bands, based on an opportunistic approach and without interfering with the licensed (primary) user. In order to identify which frequency bands are more suitable for such purposes, it is necessary to evaluate the degree in which licensed band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…However these results are location dependents. Results within this band from Mumbai [16], Hull City, UK in [29] and Romania [30] are bit lower than the values obtained. This is expected as the duty cycle in these bands are location dependent.…”
Section: Data Collection and Processingmentioning
confidence: 65%
See 1 more Smart Citation
“…However these results are location dependents. Results within this band from Mumbai [16], Hull City, UK in [29] and Romania [30] are bit lower than the values obtained. This is expected as the duty cycle in these bands are location dependent.…”
Section: Data Collection and Processingmentioning
confidence: 65%
“…Due to the low occupancies in locations 8 and 9, the activities on this band were not captured on the spectrogram. Romania [30] 5.81 2.4 -2.7…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…In Romania, corresponding to the downlink communication direction i.e. for 880 -960 GSM, E-GSM, Military bands, occupancy level was found by Authors to be 46.80% and for 1710 -1880 GSM 1800, occupancy was 22.86% [7]. A survey was conducted in Barcelona, Spain [8] to carry out a broadband spectrum measurement campaign which covered the frequency range from 75MHz to 3GHz in an outdoor urban environment.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, when the study reported in this chapter was initiated ( Table 2.1). Thenceforth, the number of reported spectrum occupancy studies in the context of DSA/CR has grown to include a greater number of locations all over the world such as Doha, Qatar [161], Bucharest, Romania [162], Amsterdam, Netherlands [163], Brno, Czech Republic [164], Paris, France [164] and some additional cities in the United States [165].…”
Section: Introductionmentioning
confidence: 99%